Wnt Signaling: Pathogen Incursion and Immune Defense - Jati, Suborno; Sarraf, Tresa Rani; Naskar, Debdut; Sen, Malini (Frontiers in Immunology, 2019)
Wnt ligands interact with the transmembrane cell surface receptors Frizzled and ROR / RYK to initiate complex signaling cascades that are crucial for cell physiology and the proper functioning of the immune system. Wnt signaling is instrumental in maintaining immune surveillance and during infections by pathogenic microbes helps mount host resistance to infection. Some pathogens, however, utilize Wnt signaling to build a niche for their survival. The goal of this review is to summarize current and developing concepts about the tug of war between Wnt signaling and pathogens for deployment of host resources, focusing mostly on macrophages and cytoskeletal actin dynamics. An additional objective is to outline the interrelation between Wnt signaling and the host microbiota, which is vital for immune defense, discussing in the same perspective, how Wnt signaling could be differentiating pathogen from non-pathogen.